The additional lateralizing and localizing value of the postictal EEG in frontal lobe epilepsy. Issue 3 (March 2016) - Whitehead, Kimberley; Gollwitzer, Stephanie; Millward, Helen; Wehner, Tim; Scott, Catherine; Diehl, Beate
Highlights: Our study revealed that 47/96 (49%) postictal periods contained lateralizing or localizing information. In 14/38 (39%) patients, at least one seizure with an unhelpful ictal EEG was followed by postictal EEG features with new lateralizing information. In frontal lobe epilepsy, close examination of the postictal EEG can offer additional information to identify a potentially resectable epileptogenic zone. Abstract: Objective: The aim of this study was to describe the additional lateralizing and localizing value of the postictal EEG in frontal lobe epilepsy (FLE). The ictal EEG in FLE is frequently challenging to localize. Methods: We identified patients investigated for epilepsy surgery with unilateral FLE based on consistent semiology, a clear lesion and/or with frontal onset on intracranial EEG. A one hour section of postictal EEG was analyzed by two raters for new or activated EEG features and it was assessed whether these features offered additional information when compared to the ictal EEG. Postictal features assessed included asymmetrical return of the posterior dominant rhythm and potentiated lateralized or regional frontal slowing, spikes or sharp waves. Results: Thirty-eight patients were included who had a combined total of ninety-six seizures. 47/96 (49%) postictal periods contained correctly lateralizing or localizing information. The sensitivity for asymmetrical return of the posterior dominant rhythm was 24%. The sensitivity for regional frontal slow and frontal spikes was 23% and 20% respectively. Further analysis showed that in 14/38 (39%) patients, at least one seizure with an unhelpful ictal EEG was followed by postictal EEG features that added new localizing or lateralizing information. A subgroup of 11 patients who were ⩾1 year seizure-free (ILAE class 1) and thus classified as having a 'gold-standard' FLE diagnosis were analyzed separately and it was found that 14/30 of their seizures (47%) had extra postictal information. Conclusions: The new postictal information was always concordant with the ultimate diagnosis, except for asymmetric postictal return of background activity ipsilateral to the epileptogenic zone in three patients. Significance: This study shows that a close examination of the postictal EEG can offer additional information which can contribute to the identification of a potentially resectable epileptogenic zone.